IMPLIKASI BATAS USIA MINIMAL CALON ANGGOTA KPU DAERAH KABUPATEN/KOTA TERHADAP HAK MASYARAKAT MILENIAL - Bagus Anwar Hidayatulloh (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
The holding of elections in Indonesia is carried out by the General Election Commission (KPU). KPU also has representatives in the Province and District / city. Recruitment of KPU Regency / City Regional Commissioner commissioners left a problem including a nomination age limit of 30 years. Implications of the age limit for prospective district / municipal KPU members on millennial community rights. Then problems arise regarding implications or impacts that can occur. So that it does not allow millennial communities to be able to register as members of the local Regency / City KPU. This rule could be contrary to the Indonesian state constitution and the reduction of the rights of millennial people as candidates for Regency / City Regional KPU members. This writing uses library collection methods and normative studies of several statutory regulations relating to age limit regulations nominating as members of the Regency / City KPU. The purpose of this paper is to find out how the implications for millennial society are mainly related to guaranteeing rights in contributing to becoming Regency / City KPU members.